TransPrint: A Method for Fabricating Flexible Transparent Free-Form Displays. (30th May 2019) - Jensen, Walther; Colley, Ashley; Häkkilä, Jonna; Pinheiro, Carlos; Löchtefeld, Markus
Abstract : TransPrint is a method for fabricating flexible, transparent free-form displays based on electrochromism. Using screen-printing or inkjet printing of electrochromic ink, plus a straightforward assembly process, TransPrint enables rapid prototyping of displays by nonexperts. The displays are nonlight-emissive and only require power to switch state and support the integration of capacitive touch sensing for interactivity. We present instructions and best practices on how to design and assemble the displays and discuss the benefits and shortcomings of the TransPrint approach. To demonstrate the broad applicability of the approach, we present six application prototypes.